The Language of Polish Tombstone Inscriptions in Cemeteries in the Ashmyany Area - Kaspiarovich, Karalina (Slavistica Vilnensis, 2025)
The article analyzes Polish-language tombstone inscriptions from cemeteries in Zhuprany, Tsudenishki, and Horodniki in the Ashmyany region of Belarus. A total of 263 inscriptions dated between 1914 and 2021 were analyzed, revealing numerous deviations from the norms of Standard Polish. The examined texts reflect both the specificity of the regional variety of the Polish language and the impact of contact with the Belarusian and Russian languages.The linguistic analysis makes it possible to distinguish features at the levels of orthography, phonetics, morphology, syntax, and lexis. These include, among others, akanye, asynchronous realization of nasal vowels, palatalization of the consonants r’, d’, and t’, the mixing of the Latin and Cyrillic scripts, the use of non-masculine personal forms and patronymic naming patterns, lexical borrowings. These differences result from centuries-long language contact and gradual shifts in the linguistic competence of younger generations.The researched material included 131 phonetic features, 99 morphological features, 76 syntactic features, 22 lexical items, and 238 orthographic variants, with orthographic phenomena accounting for 42% of the corpus. The study also identified region-specific inscription formulas absent in ethnic Polish areas.The analysis demonstrates that tombstone inscriptions serve as an important testimony to the local community’s attachment to the Polish cultural tradition, national identity, and Catholic faith.
Keywords: tombstone inscriptions; language of epitaphs; cemetery; Polish language in Belarus; Ashmyany